Monuments of Antique Architecture in Maurice Denis’ Landscapes at the Turn of the Century: in the Context of Discussion about Classical Tradition of French Art - Trusova, Polina A. (Actual Problems of Theory and History of Art, 2015)
The article deals with Maurice Denis’s landscapes devoted to the monuments of antique architecture in Italy. The landscapes were created at the turn of the century on the wave of interest in classical tradition in France. From this point of view Denis’ Italian landscapes provide a possibility to trace back the growth of Denis’ interest in ancient culture, they show his direct perception of antique monuments, give an opportunity to see a way of further interpretation of these images in his works. These landscapes are considered also in connection with new aspects in Denis’s conception of classical tradition that had a considerable impact on French art and culture at the turn of the century. Among many other articles, in which Maurice Denis presented his conception of classical tradition, the following articles should be pointed out: “Les arts à Rome ou la méthode classique” (1898), “L’influence de Paul Gauguin” (1903), “La réaction nationaliste” (1905), “Cézanne” (1907), “De Gauguin et Van Gogh au classicisme” (1909).
Keywords: Maurice Denis; French art and culture at the turn of the 20th century; classical tradition in French Art; monuments of antique architecture in landscape painting; Poussin; Cézanne